2022
DOI: 10.1002/cphc.202200166
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on the Chemiluminescence of Acridinium Thioester: A Computational Study

Abstract: Chemiluminescent labelling, which is one of the promising procedures of modern immunodiagnostics, is increasingly carried out using acridinium derivatives, an oxidant, and an alkaline aqueous environment. However, the efficiency of the chemiluminescence of luminol or acridinium esters is higher in non‐aqueous solvents such as dimethyl sulfoxide or acetonitrile. Therefore, the search for a new environment for the chemiluminescence reaction, especially the one characterized by a higher quantum yield of chemilumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 66 publications
(146 reference statements)
1
7
0
Order By: Relevance
“…As previous studies have shown [4][5][6][7]36], acridinium derivatives are easily oxidized with hydrogen peroxide in an alkaline environment. These compounds are susceptible to nucleophilic attack on the carbon atom at the 9 position of acridinium moiety.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…As previous studies have shown [4][5][6][7]36], acridinium derivatives are easily oxidized with hydrogen peroxide in an alkaline environment. These compounds are susceptible to nucleophilic attack on the carbon atom at the 9 position of acridinium moiety.…”
Section: Introductionmentioning
confidence: 79%
“…Considering our previous studies on the chemiluminescence reaction of acridinium derivatives, e.g., acridinium esters [4,5,7] or acridinium thioesters [6,36], it can be indicated that the type of leaving group is important for the efficiency of the chemiluminescence process. Comparing the energy profiles of the chemiluminescence reaction of acridinium derivatives determined by computational methods [6], it can be seen that the use of a less electronegative atom, that extends the bonds within the leaving group, results in a more efficient transformation of acridinium derivatives into electronically excited products of the CL reaction.…”
Section: Selection Of Investigated Objectsmentioning
confidence: 99%
See 3 more Smart Citations